Page kidney in a child with ureteropelvic junction obstruction of lower moiety in a partial duplex system - Hidenori Nishio; Kentaro Mizuno; Takuya Sakata; Daisuke Matsumoto; Hideyuki Kamisawa; Satoshi Kurokawa; Akihiro Nakane; Tetsuji Maruyama; Takahiro Yasui; Yutaro Hayashi (Urology Case Reports)
Reports of hydronephrosis-induced hypertension in pediatric patients are rare. A 7-year-old girl with hypertension was referred to our hospital with left hydronephrosis caused by ureteropelvic junction obstruction of the lower moiety in a partial duplex system. Because the lower moiety was almost nonfunctional, a laparoscopic heminephrectomy was performed. Antihypertensive drugs were unnecessary on the day after surgery. This is the first report of a Page kidney in a patient with ureteropelvic junction obstruction of the lower moiety. The cause of hypertension was evaluated based on the plasma renin activity and pathological findings of the lower moiety.